Developing a fashion collection - Renfrew, Elinor; Renfrew, Colin (Basic fashion design, 2016)
"Fully updated with new interviews and inspiring images, the 2nd edition of Developing a Fashion Collection covers everything the fashion student needs to know before designing their own collections. Developing a Fashion Collection focuses on the process of designing a collection, and explores different types of research, fabric sourcing, the key roles within a design team and the many sources of inspiration available to designers. Different market levels from ready-to-wear to online shopping are covered in-depth, and are given real-world context through insightful interviews with practising contemporary designers. Collections for niche markets, including knitwear, childrenswear and footwear are also discussed. The 2nd edition of Developing a Fashion Collection features interviews with high-profile international contemporary fashion designers, including Sister by Sibling, Holly Fulton, Todd Lynn, thefuturelaboratory, People Tree, Leutton Postle and Insley & Nash"--Resumé vydavatele